PENGARUH MODAL INTELEKTUAL DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Yoesef Ellyabraham; Nugroho Mardi Wibowo; Hadi Susanto (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this study is to describe and analyze intellectual capital and ownership structure on the value of Property and Real Estate companies through financial performance. Research is used with a descriptive type with a quantitative research approach. The population is 48 Property and Real Estate Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. a sample of 18 companies with purposive sampling technique. This study uses Partial Least Square (PLS) analysis. The results show that intellectual capital has a significant effect on the company's financial performance, ownership structure has no significant effect on the company's financial performance, intellectual capital has no significant effect on firm value, ownership structure has a significant effect on firm value, financial performance has a significant effect on firm value, intellectual capital has no significant effect on firm value. has a significant effect on company value through company financial performance, and capital structure has no significant effect on company value through company financial performance.